Utilization of Education Hotel (Edotel) as A Learning Resource for Students of the Hospitality Accommodation Skills Competency Program at Vocational Schools - Fauzan Ari Kurniawan; Theerapong Sangpradit; Tinku De Gope (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This study explores the use of Edotel as a learning resource for students specializing in the Front Office and Housekeeping within the accommodation and hotel expertise competency program at Vocational High School 4 Yogyakarta. Methodology: The study employed a survey method and was conducted at Vocational High School 4 Yogyakarta. The research population included 102 students, and a proportional random sampling technique was used to select a sample of 78 students. Main Findings: The study focused on Grades XI and XII students. In the Front Office specialization, 70.51% of students rated the learning resource as good, 15.39% as poor, and 1.28% as very poor, based on indicators such as room reservation, guest services, information services, check-in/check-out, and cashier services. In the Housekeeping specialization, 20.51% of students rated it as very good or good, while 79.49% rated it as poor or very poor, based on indicators like executive housekeeping, guest rooms, public rooms, linen, and laundry sections. Novelty/Originality of this study: This research highlights the innovative use of Edotel as a learning resource for students in the hospitality accommodation skills competency program at Vocational School 4 Yogyakarta, presenting several significant advancements compared to previous studies.